Implementasi Waterfall Pada Sistem Monitoring Bimbingan Konseling Siswa Berbasis Web Mobile - Davit Irawan; Fido Rizki; Yani Kurnia (STIKes Ibnu Sina Ajibarang, 2023)
Currently processing counseling guidance data still uses manual methods, that is, every time there is a violation of the rules and regulations committed by students, it will be recorded by the BK (Counseling Guidance) teacher or officer using paper media, because there are so many violations that this school has difficulty in processing it. counseling guidance data and the use of paper as a medium for recording violations is no longer relevant, and also the less effective function of parental summons letters which are rarely delivered by students who violate school rules, the aim of this research is to build a monitoring system for counseling guidance in SMPN Selangit is based on mobile web to make it easier for the school to process student violation data, the system development method used in this research is waterfall, waterfall is a method that provides systematic and sequential approaches for software developers such as requirements specifications, software design implementation , trials, and so on, the implication of this research is that the existence of this counseling guidance information system can make it easier for the school to process counseling guidance data and make it easier for parents to monitor their children at Selangit Middle School.